2014
DOI: 10.1371/journal.pone.0111375
|View full text |Cite
|
Sign up to set email alerts
|

IL22 Regulates Human Urothelial Cell Sensory and Innate Functions through Modulation of the Acetylcholine Response, Immunoregulatory Cytokines and Antimicrobial Peptides: Assessment of an In Vitro Model

Abstract: Human urinary disorders are generally studied in rodent models due to limitations of functional in vitro culture models of primary human urothelial cells (HUCs). Current HUC culture models are often derived from immortalized cancer cell lines, which likely have functional characteristics differ from healthy human urothelium. Here, we described a simple explant culture technique to generate HUCs and assessed their in vitro functions. Using transmission electron microscopy, we assessed morphology and heterogenei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Understanding the roles these peptides play in the lower urinary tract requires significantly more study; however, they are likely to play a key role in microbial community regulation, resilience following dysbiotic/infection episodes and response to treatment for lower urinary tract disorders. Similarly, the recent detection of IL-22 receptors in the urothelium allows consideration of interactions between the microbial community, known urothelial cholinergic receptors, the non-barrier role of the urothelium, and AMPs [23]. Interpretation of these interactions may provide new insights into important immune functions of the bladder.…”
Section: Immune Functions Of the Bladdermentioning
confidence: 99%
“…Understanding the roles these peptides play in the lower urinary tract requires significantly more study; however, they are likely to play a key role in microbial community regulation, resilience following dysbiotic/infection episodes and response to treatment for lower urinary tract disorders. Similarly, the recent detection of IL-22 receptors in the urothelium allows consideration of interactions between the microbial community, known urothelial cholinergic receptors, the non-barrier role of the urothelium, and AMPs [23]. Interpretation of these interactions may provide new insights into important immune functions of the bladder.…”
Section: Immune Functions Of the Bladdermentioning
confidence: 99%
“…They also determined that AMP activity was significantly more robust in individuals whose day-of-surgery standard urine cultures were positive for typical uropathogens or in individuals whose standard urine cultures became positive following surgery [16]. In an attempt to understand mechanism, another team reported that the cytokine interleukin-22 regulates human urothelial cell sensory and innate functions by modulating AMP synthesis [25]. Given the new knowledge that the FUM exists and the detection of AMPs within the adult urinary tract [26], it will be essential to clarify the physiologic role of urinary AMPs in health and disease.…”
Section: Introductionmentioning
confidence: 99%
“…and Streptococcus is a genus that most widely reported as urinal microbiota and exist in the whole study that published this moment as an acid lactate bacteria genus that related with some body tissue especially urinary tract where they play a role as aprotector against pathogens. 12 The correlation between the amount of Lactobacillus spp colony with overactive bladder events with statisticstests done in this study obtained the result was not significant. This events could due by other factor that cause the occurrence of OAB as myocyte damage in the destrusor muscle, damage in inhibitor path in brain and marrow spine or damage insensitivity terminal afferents in biological urinary, UTI, estrogen deficiency and systemic abnormalities.…”
Section: Discussionmentioning
confidence: 50%